The effect of betel nut extract on melanin pigment levels in rats' skin exposed to Ultraviolet B radiation - Putri, Aisy; Pulungan, Ica Yulianti; Napitupulu, Olivia Des Vinca Albahana (Jurnal Prima Medika Sains, 2024)
This study aims to analyze the effect of areca nut extract on the amount of melanin pigment in the skin of Wistar rats exposed to ultraviolet-B light. The research method used was post-test with control group design. The total sample of white rats used was 20 rats, which were divided into 4 groups with each group consisting of 5 rats. The cream preparation was made using cold cream base. The rats were then exposed to UVB with a certain intensity for 5 days, characterized by erythema as a result of UVB absorption into the epidermis. Each group of treated rats received base cream, 10% areca nut extract cream, and 15% areca nut extract cream topically for 14 days before termination on day 15. The collected data were then tabulated and analyzed. To determine significant differences or influences between the test groups, analysis was carried out with t-test or Independent Samples T-Test approach at 95% confidence level (p < 0.05). The results of the analysis showed that the administration of areca nut extract was effective in reducing the amount of melanin pigment in the skin of Wistar rats exposed to Ultraviolet-B light. From histopathological observations, the administration of areca nut extract with a concentration of 15% is effective in removing or fading melanin pigments in the skin exposed to Ultraviolet-B light and the results of damaged skin melanin pigments appear in the epidermis of rat skin barely visible grain.